Simulasi Kebijakan Penambahan Areal Tanam dan Peningkatan Produktivitas dalam Mendukung Tercapainya Swasembada Jagung - Parama Tirta Wulandari Wening Kusuma; Didik Junaedi Rachbini (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2019)
Corn is one of five main commodities that is expected to achieve self-sufficiency at the end of RPJMN 2019. However, the gap between supply and demand capacities was still quite large, so that imports are still conducted. The government through the Ministry of Agriculture issued a self-sufficiency policy through extensification and intensification, with the scenario of Planting Areas increase (PAT) of up to 3 million Ha, and productivity increase of up to 53.18 Ku/Ha. This study aims to: (1) measure the achievement of national corn self-sufficiency by establishing a model of national corn availability dynamic system before and after the self-sufficiency policy; (2) develop some policy alternatives for corn self-sufficiency. This article used a dynamic system approach based on secondary data from the Ministry of Agriculture and BPS, determined dynamic hypotheses and systems models, made causal loop diagrams, calculated stock flow diagrams, and validated and verified the models. The results of validation and verification illustrated that the model was made in accordance with the actual conditions that exist. The simulation results showed that increasing the cropping index can continuously achieve maize self-sufficiency until 2019, as well as the scenario of realistic, optimistic extensification (PAT) and the combination of realistic and intensification.